Analisis Pengaruh Brand Loyalty, Brand Quality, dan Marketing Communication terhadap Keputusan Pembelian Kosmetik MS Glow Jogja-Bantul - Ida Bagus Nyoman Udayana; Febriani Wahyu Saputri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine how the influence of brand loyalty and brand quality on the purchase of MS Glow Products, and to find out and how the consumer's purchasing decisions at the MG Glow Jogja-Bantul store. This research is a quantitative research using survey method until the population in this study are consumers of MS Glow Jogja-Bantul products. Collecting data using a questionnaire method that has been tested for validity and reliability. The data that has been collected, then carried out data testing, model testing and hypothesis testing SPSS is used for data analysis and for sampling as many as 53 people so that validity and reliability can be tested. Based on the results of the analysis and discussion, the authors conclude that Brand and Marketing Communication together have a positive and significant effect on consumer purchasing decisions on MS Glow Beauty Products Jogja-Bantul. Keywords: Brand Loyalty, Brand Quality, Marketing Communication, Purchase decision